LINE-1 Retrotransposition Activity in Human Genomes - Beck, Christine R. (2010)
Long Interspersed Element-1 (LINE-1 or L1) sequences comprise the bulk of retrotransposition activity in the human genome; however, the abundance of highly active or ‘hot’ L1s in the human population remains largely unexplored. Here, we used a fosmid-based, paired-end DNA sequencing strategy to identify 68 full-length L1s which are differentially present among individuals but are absent from the human genome reference sequence. The majority of these L1s were highly active in a cultured cell retrotransposition assay. Genotyping 26 elements revealed that two L1s are only found in Africa and that two more are absent from the H952 subset of the Human Genome Diversity Panel. Therefore, these results suggest that ‘hot’ L1s are more abundant in the human population than previously appreciated, and that ongoing L1 retrotransposition continues to be a major source of inter-individual genetic variation.